An Analysis of Students’ Creative Thinking Skills in IPAS Learning for Fifth-Grade Students at SD Negeri 01 Ulakkarang Selatan - Jessyca Tania Lubis; Stavinibelia Stavinibelia; Nofriza Efendi; Rica Azwar (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Thinking ability is not only about generation new ideas but also involves the ability to see relationships between concepts, ask critical questions, and produce original solutions. This study aims to analyze the creative thinking skills of fifth-grade students in IPAS (Natural and Social Sciences) learning at SD Negeri 01 Ulak Karang Selatan. Using a qualitative approach with a descriptive method, data were collected through observation, interviews, and documentation. The results show that the manifestation of students' creative thinking skills varies. Fluency is the most prominent indicator, while flexibility and originality are still limited. The ability for elaboration tends to align with the uniqueness of an idea. Although the teacher has implemented strategies to encourage creativity, such as using open-ended questions and simple project assignments, their implementation still faces major obstacles like limited time, inadequate facilities, and students' passive habits. Thus, this study concludes that students' creative potential has not been optimally explored. A commitment from the school is needed to provide resources and teacher training to support the continuous development of creative thinking skills.